Massive parallel IGHV gene sequencing reveals a germinal center pathway in origins of human multiple myeloma - Cowan, Graeme; Seckinger, Anja; Hose, Dirk (OncoTarget, 2015)
Oncotarget | https://doi.org/10.18632/oncotarget.3644 Graeme Cowan, Nicola J. Weston-Bell, Dean Bryant, Anja Seckinger, Dirk Hose, Niklas Zojer, Surinder S. Sahota